Telemonitoring in Heart Failure Management - Ivo Planinc; Davor Milicic; Maja Cikes (Cardiac Failure Review)
Telemonitoring (TM) aims to predict and prevent worsening heart failure (HF) episodes and improve self-care, patient education, treatment adherence and survival. There is a growing number of TM options for patients with HF, but there are numerous challenges in reaching positive outcomes. Conflicting evidence from clinical trials may be the result of the enormous heterogeneity of TM devices tested, differences in selected patient populations and variabilities between healthcare systems. This article covers some basic concepts of TM, looking at the recent advances in the most frequently used types of TM and the evidence to support its use in the care of people with HF.